Clinical, pathological, and radiological features of 80 pediatric diffuse intrinsic pontine gliomas: A single-institute study - Zhang, Peng; Duan, Yunyun; Gu, Guocan; Qu, Liying; Xiao, Dan; Xi, Tianshu; Pan, Changcun; Liu, Ya’ou; Zhang, Liwei (Frontiers in Oncology, 2023)
Objective Diffuse intrinsic pontine gliomas (DIPGs) are rare but devastating diseases. This retrospective cross-sectional study aimed to investigate the clinical, radiological, and pathological features of DIPGs. Materials and methods The clinical data of 80 pediatric DIPGs under clinical treatment in Beijing Tiantan Hospital from July 2013 to July 2019 were retrospectively collected and studied. A follow-up evaluation was performed. Results This study included 48 men and 32 women. The most common symptoms were cranial nerve palsy (50.0%, 40/80 patients) and limb weakness (41.2%, 33/80 patients). Among the 80 patients, 24 cases were clinically diagnosed, 56 cases were pathologically verified, and 45 cases were tested for H3K27 alteration status, with 34 H3K27 alteration cases confirmed. Radiological results indicated that enhancement was common (65.0%, 52/80 patients). Cho/Cr was of predictive value for H3K27 alteration status (P = 0.012, cutoff value = 2.38, AUC = 0.801). Open cranial surgery followed by further chemotherapy and radiotherapy was beneficial for patients’ overall survival. Cox regression analysis indicated H3K27 alteration to be the independent prognostic influencing factor for DIPGs in this series (P = 0.002). Conclusion DIPGs displayed a wide spectrum of clinical and imaging features. Surgery-suitable patients could benefit from postoperative comprehensive therapy for a better overall survival. H3K27 alteration was the independent prognostic influencing factor for DIPGs.